Whole-genome sequencing analysis of salmonella isolates from poultry farms, a slaughterhouse, and retail stalls in Thailand - Ong, Kar Hui (2022)
The draft genome sequences of 21 Salmonella isolates obtained from poultry production chains in Hat Yai City, Songkhla Province, Thailand, are reported in this study. Our study revealed that there was Salmonella environmental contamination along poultry production chains and cross-contamination among poultry through inanimate surfaces in the environment.